1993
DOI: 10.1002/1097-0142(19930801)72:3<850::aid-cncr2820720334>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Gliosarcoma with features of chondroblastic osteosarcoma

Abstract: Background. The occurrence of osteoid‐chondral elements in gliosarcoma is extremely rare and has been reported in only two cases. A new, rare case of gliosarcoma with osteosarcomatous differentiation in a 55‐year‐old man and histogenesis of osteoid‐chondral tissue in gliosarcoma is discussed. Methods. Surgically removed tumor tissues were examined immunohistochemically and electron microscopically, and a histologic examination was performed. Results. Immunohistochemical and electron microscopic studies confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…9 In our study, all cases of osteosarcomas were positive for GFAP. The strongest expression was documented in tumors with chondroblastic differentiation.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…9 In our study, all cases of osteosarcomas were positive for GFAP. The strongest expression was documented in tumors with chondroblastic differentiation.…”
Section: Discussionsupporting
confidence: 53%
“…[2][3][4][5][6] GFAP is the most specific marker for cells of astrocytic origin under normal and pathological conditions. By immunohistochemistry, however, GFAP has been shown to be expressed in mesenchymal tumors, such as soft tissue myoepitheliomas, peripheral nerve sheath tumors, and chordomas, 3,[7][8][9][10][11][12] and also in mixed tumors, such as salivary gland pleomorphic adenomas. 13,14 These findings can create problems for the diagnosis of tumors that have similar morphologies and are positive for GFAP, such as myoepithelioma and chondroblastic osteosarcoma of the head and neck.…”
mentioning
confidence: 99%
“…Epithelial differentiation with carcinomatous features can also occur in glial portions [115]. The sarcomatous component of this tumour shows atypical, aggressive features and can differentiate along multiple distinct lineages, such as fibroblastic, osteogenic, chondrogenic, adipogenic, and myogenic types, especially upon exposure to radiation treatment [2,7,8,10,52,89,139]. A similar potential variant termed gliofibroma has also been described consisting of biphasic glial and non-sarcomatous fibroblastic components commonly found in paediatric patients [89].…”
Section: Gliosarcomamentioning
confidence: 99%
“…Some studies indicate that osteosarcoma cells also arise from progenitor stem cells, although the particular stem cell has not been identified but it is thought to be an osteoprogenitor cell capable of differentiating into phenotypes seen in cartilage and bone [9,17,19,20,55]. We suggest the stem cells giving rise to the cancer may be more primitive than an immediate progenitor cell, ie, a multipotent stem cell.…”
Section: Introductionmentioning
confidence: 85%
“…Ewing's sarcoma contains cells with mesenchymal, epithelial, and neural features [9,10,46]. Sarcoma cells promote neuronal and glial differentiation [19,21,22], which means that the cells with these markers in Ewing's sarcoma could have arisen from nonsarcoma cells. However, none of these studies showed that osteosarcoma cells could differentiate to phenotypes other than cartilage or bone.…”
Section: Introductionmentioning
confidence: 99%